A Preliminary Study on Pain Reduction and Shorter Length of Stay on Grade III of Internal Hemorrhoid Patients Undergoing HAL-RAR (Haemorrhoid Arteri Ligation with Recto Anal Repair) with no Doppler Guided Technique - Budhi Ida Bagus; Metria Ida Bagus; Setyawati Ida Ayu (Iranian Journal of Colorectal Research, 2022)
Background: Many technique has been announced in managing the internal haemorrrhoid cases, HAL-RAR is safe and almost painless technique and it has very good results in the control of haemorrhoidal symptoms. This procedure should be considered as an effective first treatment option for haemorrhoids. The most common problem which should be discussed was the cost of this procedure, especially in routine clinical practice. We would reported the safety and effectiveness of the HAL-RAR with no Doppler guided on stage III internal haemorrhoid in single centre teaching hospital.Methods: As a modification from the standard HAL-RAR procedure with doppler guided, we will evaluated the clincal outcome of this technique on grade III of internal hemorrhoid patients. All patients with no previous hemorrhoid surgery will be included on this study. The patients whose associated with procititis and colorectal cancer will be excluded.Results: We reported our first 61 patients with grade III internal haemorhoid managed using modified HAL-RAR technique without Doppler guided performed during the procedure. This technique was acceptable well by the patients, pain controlled could be achieved early in the first post operative day. The average pain score (using Visual Analog Score) before discharged was 1,77 and the average length of stay was 1,36 days with no post operative bleeding found during follow up period. Conclusion: HAL-RAR with no Doppler guided technique was safe and effective in reducing pain and the length of stay with tolerable pain controlled.